The dancer in the eye: towards a multi-layered computational framework of qualities in movement - Camurri, A.; Volpe, G.; Piana, S.; Mancini, M.; Niewiadomski, R.; Ferrari, N.; Canepa, C. (Proceedings of the 3rd International Symposium on Movement and Computing, 2016)
This paper presents a conceptual framework for the analysis of expressive qualities of movement. Our perspective is to model an observer of a dance performance. The conceptual framework is made of four layers, ranging from the physical signals that sensors capture to the qualities that movement communicate (e.g., in terms of emotions). The framework aims to provide a conceptual background the development of computational systems can build upon, with a particular reference to systems analyzing a vocabulary of expressive movement qualities, and translating them to other sensory channels, such as the auditory modality. Such systems enable their users to "listen to a choreography" or to "feel a ballet", in a new kind of cross-modal mediated experience.